THE RESTORATIVE JUSTICE APPROACH TO THE IMPLEMENTATION OF CHILDREN'S CRIMINAL JUSTICE SYSTEM IN INDONESIA - Ali Muhammad (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Since the enactment of Law No. 11 of 2012 concerning the Criminal Justice System for Children in Indonesia needs to be sought immediately for Law Enforcement Officials (APH) who do not understand and know about the obligation to adopt a Restorative justice approach in the implementation of the Child Criminal Justice System. The norm that regulates the obligation to approach restorative justice in the handling of Children dealing with the Law (ABH) contained in article 5 paragraph 1 of the Child Criminal Justice System Law and this Law has also adopted the International instrument of the Convention on the Rights of the Child (CRC) ratified by the government of the Republic of Indonesia with a Presidential Decree Number 36 of 1990 concerning Ratification of the Convention on the Rights of the Child in addition to other international regulations such as the Beijing Rules, Riyadh Guidelines and Tokyo Rules which are certainly in line with the Constitution 1945 concerning the purpose of the country which was wrong was to realize social justice and promote public welfare. This restorative justice approach certainly has the same spirit as the ideological values ​​of Pancasila, politics, and the Indonesian national socio-culture which prioritizes solutions through deliberation to reach consensus so that this restorative justice approach is also one of legal reforms that elevates the values ​​of local wisdom from the Nation Indonesia. The conceptual approach and the approach to legislation (the statue approach) are the approaches used in this study and maximize the implementation of the implementation of restorative justice in every handling of children facing the law (ABH) at each stage of the investigation, prosecution and trial. research is to provide confirmation to every Law Enforcement Officer of the obligation to take a Restorative Justice approach in every Handling of ABH.